Leadership in the Time of COVID: Connecting Community Resources to Meet the Needs of North Carolina Students - Price, Douglas C.; Mansfield, Katherine Cumings (Frontiers in Education, 2021)
The purpose of this article is to share what we learned conducting an exploratory pilot study on how school leaders in North Carolina responded to changes wrought by the onset of the novel Coronavirus in early 2020. In many ways, North Carolina is a distinctive case because it exists in what is commonly referred to as the Urban/Rural Divide; but, it is also similar to other cases in that educators must be adaptable and flexible in a situation that is constantly in flux. As a result, some findings confirmed our hunches about how educators were faring in this new world we face. Other discoveries, however, were truly that: discoveries, leading us to two new areas of future research: 1) examining more deeply the weighty connections between past political decisions around public infrastructure (e.g. broadband) and many of the current crises facing school leaders; and 2) continuing to expand our collection of cases that illustrate ways a broad collection of community stakeholders can emerge as educational leaders when barriers are removed, critical thinking and timeliness is employed, and the best interest of the students is central to thought processes.